Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste